Izbrana poglavja iz mehanike tal - Jelušič, Primož (University of Maribor Press, 2021)
Selected Chapters from Soil Mechanics. The objective of the book is to present the basic procedures for evaluating the physical and mechanical properties of soils, which are the basis for effective problem solving in geotechnical engineering. The book provides laws that describe the physical and mechanical properties of soils. The contents of Soil Mechanics are interrelated, making it difficult to separate them into individual chapters. According to the existing literature in the field of soil mechanics, the contents of the book are divided into 16 chapters: Introduction, Soil Classification, Three-Components of Soil, Stresses in Soil, Stresses in Soil Layer, Darcy’s Law, Soil Permeability, Groundwater Seepage, Stresses and Strains, One-Dimensional Compression, Consolidation, Creep, Shear Strength, Determination of Shear Strength Parameters, Elastic Stresses and Deformations, and Stability Analysis.